Solver as a financial asset allocation tool - Rodrigues Matsumoto, André; Bruno Lopes de Souza Brito, Giovanni; Luz da Conceição, Marcio; Ferreira de Oliveira Junior, Waldecy; Aragão Ferreira Silva , Paola; Yani Figueira de Holanda, Genifer; Cavalcante Saldanha, Dayanne; Filipe Lima Raposo, Cláudio (Seven Editora, 2023)
The definition of an investment portfolio usually depends on the elaboration of a strategy, which may or may not be successful in its results. Obviously, in this context, there will be an arrangement with the allocated assets, according to the idealized strategy. That said, naturally arises the need to have good instruments to assist in the configuration of this investment portfolio. To fulfill this purpose, Microsoft Excel’s Solver tool emerges as an interesting candidate to meet this demand, being able to facilitate the search for the best combination of financial assets, given a certain level of risk, or Beta. The objective of the study was to verify the feasibility of using the solver tool in the construction of an investment portfolio, seeking to reduce or even eliminate the diversifiable risk. This study is characterized as an experiment, of an exploratory nature, of a quantitative nature, and the results were obtained through simulation in Microsoft’s software. The information that guided the research was obtained from an electronic site, scientific article and newspaper. It was found that Solver was able to meet the objective, according to the adoption of the desired parameters, however, to strengthen the understanding, it is still necessary to increase the set of financial assets, which have negative correlations with each other as a characteristic. DOI: 10.56238/pacfdnsv1-116